Mpox Masquerading as Secondary Syphilis. (April 2023) - Whealon, Candice
Abstract : Mpox is a great masquerader requiring emergency nurse practitioners to rely on their clinical acumen to accurately diagnose and treat this public health emergency. The disease is nearly indistinguishable from other pox viruses and similar in presentation to several viral and bacterial infections associated with enanthems and exanthems. The most recent outbreak disproportionally affects men who have sex with men, particularly those individuals with HIV. Early recognition and intervention are key; however, clinicians' lack of knowledge, limited access to testing, and unfamiliarity with appropriate medications and vaccines historically reserved for smallpox create a barrier to treatment. Emergency nurse practitioners must gain an understanding of this disease to provide the care and anticipatory guidance to prevent associated morbidity, mortality, and spread of mpox.